Therapeutic effects of anti‐GM2 CAR‐T cells expressing IL‐7 and CCL19 for GM2‐positive solid cancer in xenograft model - Takahiro Sasaki; Yukimi Sakoda; Keishi Adachi; Yoshihiro Tokunaga; Koji Tamada (Cancer Medicine, 2023)
Abstract Background While chimeric antigen receptor (CAR)‐T cell therapy has demonstrated excellent efficacy in hematopoietic malignancies, its clinical application in solid cancers has yet to be achieved. One of the reasons for such hurdle is a lack of suitable CAR targets in solid cancers. Methods GM2 is one of the gangliosides, a group of glycosphingolipids with sialic acid in the glycan, and overexpressed in various types of solid cancers. In this study, by using interleukin (IL)‐7 and chemokine (C‐C motif) ligand 19 (CCL19)‐producing human CAR‐T system which we previously developed, a possibility of GM2 as a solid tumor target for CAR‐T cell therapy was explored in a mouse model with human small‐cell lung cancer. Results Treatment with anti‐GM2 IL‐7/CCL19‐producing CAR‐T cells induced complete tumor regression along with an abundant T cell infiltration into the solid tumor tissue and long‐term memory responses, without any detectable adverse events. In addition, as measures to control cytokine‐release syndrome and neurotoxicity which could occur in association with clinical use of CAR‐T cells, we incorporated Herpes simplex virus‐thymidine kinase (HSV‐TK), a suicide system to trigger apoptosis by administration of ganciclovir (GCV). HSV‐TK‐expressing anti‐GM2 IL‐7/CCL19‐producing human CAR‐T cells were efficiently eliminated by GCV administration in vivo. Conclusions Our study revealed the promising therapeutic efficacy of anti‐GM2 IL‐7/CCL19‐producing human CAR‐T cells with an enhanced safety for clinical application in the treatment of patients with GM2‐positive solid cancers.